2006
DOI: 10.2165/00003088-200645070-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Approach for the Scaling of Clearance in Children

Abstract: Paediatric clinical trial development could greatly benefit from clearance scaling, particularly in guiding dosing regimens. Furthermore, since the proportion of clearance via different elimination pathways is age-dependent, information could be gained on the developmental extent of drug-drug interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
196
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(206 citation statements)
references
References 176 publications
9
196
1
Order By: Relevance
“…The GFR (child) was calculated using a postmenstrual age model,31 and f u(child) was estimated using an age‐specific model considering plasma protein concentrations in children and the affinity of drugs for binding proteins 30, 32. Reabsorption (GFR fraction) was assumed to have no ontogeny.…”
Section: Methodsmentioning
confidence: 99%
“…The GFR (child) was calculated using a postmenstrual age model,31 and f u(child) was estimated using an age‐specific model considering plasma protein concentrations in children and the affinity of drugs for binding proteins 30, 32. Reabsorption (GFR fraction) was assumed to have no ontogeny.…”
Section: Methodsmentioning
confidence: 99%
“…At present no specific information about ontogeny in humans is available for UGT2B15, whereas some information is available on other UGT isoforms, such as UGT1A1, the activity of which is low at birth, reaching levels comparable to adulthood within 3-6 months later (de Wildt et al, 1999), or UGT2B7 whose activity in neonates at term is only 5% that of adults, increases to 30% by 3 months of age, and reaches adult levels by 1 year of age (Edginton et al, 2006). This pattern is the one which has been used in human PBPK models to account for possible limited UGT activity for BPA conjugation during early life (Edginton and Ritter, 2009;Mielke and Gundert-Remy, 2009).…”
Section: The Enzymes Involved In Bpa Biotransformationmentioning
confidence: 99%
“…Nonetheless, it is important to note that modelling of renal drug disposition in paediatrics requires special consideration to account for the maturation of renal function and ontogeny of protein expression. For those interested in this topic, modelling efforts and reviews have previously been reported (7)(8)(9). Another topic outside the scope of the current review is research into renal disposition in preclinical species.…”
Section: Introductionmentioning
confidence: 99%